Incidence of Heterobasidion spp.in Scots pine on "low risk" sites in Southern Sweden - Dambrauskaite, Milda (SLU/Southern Swedish Forest Research Centre, 2019)
Heterobasidion spp. fungi cause pathogenic infections in woody plants throughout the northern hemisphere, causing the most damage in the Boreal forest zone. In Sweden Scots pine, being the second most economically important tree species, suffers a considerable amount of damage as Heterobasidion spp. fungal infections hinder the annual increment of a tree. This causes significant financial losses.